Selectins in Liver Ischemia and Reperfusion Injury. (3rd September 2015) - Jones, Ryan T.; Toledo-Pereyra, Luis H.; Quesnelle, Kelly M.
ABSTRACT: Liver ischemia reperfusion injury is mediated by a complex system of signaling cascades and inflammatory response resulting in organ damage. Selectins are a group of cell adhesion glycoproteins that play a key role in the initial immunological response. L-selectins, found on leukocytes, initiate the original adhesion and rolling phase of leukocyte extravasation upon liver sinusoidal endothelial cells (LSECs). P-selectins, found on platelets and tissue-specific endothelial cells, further increases leukocyte-endothelial adhesion and rolling. P-selectin-ligand binding also initiates intracellular signals that produce adhesion molecules to start firm adhesion and increase local chemokine production. L-selectin-ligand binding on the leukocytes increases adhesion molecule expression and chemokines, but also initiate changes in intracellular structural actin. E-selectin expression occurs with the presence of TNF-α and/or IL-1β. E-selectin-ligand binding decreases leukocyte rolling velocity and increases adhesion molecules. Together, these glycoproteins transition the leukocyte response from original margination and rolling to firm adhesion and eventually migration.